Determining content reliability in Qur’anic studies using Cohen’s Kappa index - Mohd, Nor Syamimi; Hussin, Haziyah; Ahmad, Nadzrah (Perbadanan Kota Buku, 2020)
Document analysis, interview transcription and observation fieldnotes are the most popular and rapidly expanding techniques for collecting data in a qualitative research, especially in Qur’anic studies. These techniques have been applied to many areas of inquiry and has been used to study the methodology of Qur’anic exegesis, the exegetes’ thought and the thematic interpretation of the Qur’an. However, occasionally the process of collecting and analysing data is not properly done, and this could affect credibility and accuracy of a description, explanation or finding of a research. Thus, the Cohen’s Kappa Index is suggested to be applied to provide a scientific, valid and reliable research in the Qur’anic studies. The purpose of this chapter is to highlight a few examples of Qur’anic research that applied the Cohen’s Kappa Index to ascertain the validity and reliability of those qualitative studies. Those examples would provide appropriate guidance in the use of the Index in other areas of qualitative research.